Toward Universal Access to Clean Cooking and Heating : Early Lessons from the East Asia and Pacific Clean Stove Initiative - Zhang, Yabei; Adams, Norma (World Bank, Washington, DC, 2016)
Early Lessons from the East Asia and Pacific Clean Stove Initiative Initial lessons from the East Asia and Pacific (EAP) Clean Stove Initiative (CSI) confirm the need for country-specific roadmaps, strong national support, well-targeted subsidies, and integration of local conditions and international best practices into stoves standards and testing protocols. Pilot results suggest that results-based financing is a promising way to incentivize the clean stoves market. Linkage with other projects having clean stoves components could accelerate scaled-up implementation.